Efectos de la aplicación de tres niveles de fertilización química y dos bioestimulantes radiculares del cultivo de cebada (Hordeum vulgare L.), en el cantón Mira, provincia del Carchi - Bolaños Vallejo, Lilian Mercedes (2015)
In the community of Pisquer, parish Mira, Mira canton, province of Carchi this work was performed in order to evaluate the effect of the application of three levels of chemical fertilization and two root stimulators on agronomic performance and crop yield barley (Hordeum vulgare L). Seven treatments combined by 30-30-15 NPK levels was investigated; 60-60-30 and 90-90-45 combined with two bioestimulantes Raizal and Kelpak in doses of 2 kg / ha and 2 L/ha respectively. Design Randomized Complete Block (DBCA) was used in factorial arrangement A x B + 1 with 7 treatments and three replications, giving a total of 21 experimental units. The total area of the experiment was 576.00 m2, experimental plots of 16.00 m2 with a useful area of 12.00 m2. It was evaluated, plant height, stem thickness, number of shoots per seed, root length, root weight, number of grains per panicle and grain yield. Data variance analysis and comparison underwent treatments hiso with Duncan test 5%........